Values and physical activity among sports science students in France and China: a transcultural analysis - Liang, Yan; Rascle, Olivier; Hanel, Paul H. P.; Yang, Jian; Souchon, Nicolas (Frontiers in Psychology, 2024)
Objective. The aim of this study was to analyze the relations between values and physical activity in France (a West European individualistic country) and in China (an East Asians collectivist country). Method. Six hundred and twenty-seven sport sciences students completed in France (N=308, Mage=18.99, SD=1.64) and in China (N=319, Mage=20.44, SD=1.09) the International Physical Activity Questionnaire long version (IPAQ long, Craig et al., 2003) and the Portrait Values Questionnaire of Schwartz et al.'s (2012) refined values theory (PVQ-RR).Results. The same way in France and in China, moderated regression analysis revealed that hedonism predicted positively physical activity, while security-societal, security-personal, and conformity-rules values predicted negatively physical activity. In contrast, stimulation and universalism nature values predicted positively physical activity only in France. In China, benevolence, benevolence caring predicted positively physical activity, while power dominance predicted negatively physical activity. Additionally, we found evidence for measurement invariance of the value questionnaire.Discussion and conclusion. Our findings add to the literature by showing that the valuebehavior link is partly the same across countries and partly different. Further, our findings show that for certain populations the previously established hierarchy of human values does not replicate.